2017
DOI: 10.1080/10872981.2017.1314751
|View full text |Cite
|
Sign up to set email alerts
|

When less is more: validating a brief scale to rate interprofessional team competencies

Abstract: Background: There is a need for validated and easy-to-apply behavior-based tools for assessing interprofessional team competencies in clinical settings. The seven-item observer-based Modified McMaster-Ottawa scale was developed for the Team Objective Structured Clinical Encounter (TOSCE) to assess individual and team performance in interprofessional patient encounters.Objective: We aimed to improve scale usability for clinical settings by reducing item numbers while maintaining generalizability; and to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…These eight faculty members also evaluated the videos using the Interprofessional Collaborator Assessment Rubric (ICAR) and Modified McMaster-Ottawa (MMO) four-item scale to test the convergent and divergent validity of the PICT. 11,12 The ICAR and MMO were chosen for comparison with the PICT because of the overlap in the interprofessional criterion each measures as well as other aspects that made them less than ideal for use at our college. For instance, the MMO only has three competency levels, but other observer-based assessment tools used for skills-based assessment at the college had four competency levels.…”
Section: Methodsmentioning
confidence: 99%
“…These eight faculty members also evaluated the videos using the Interprofessional Collaborator Assessment Rubric (ICAR) and Modified McMaster-Ottawa (MMO) four-item scale to test the convergent and divergent validity of the PICT. 11,12 The ICAR and MMO were chosen for comparison with the PICT because of the overlap in the interprofessional criterion each measures as well as other aspects that made them less than ideal for use at our college. For instance, the MMO only has three competency levels, but other observer-based assessment tools used for skills-based assessment at the college had four competency levels.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of included articles demonstrated that the nursing profession was the most frequently represented (n = 27), 22‐48 followed by medicine (n = 20), 24,26,27,29,30,32,34‐36,38,40‐44,46‐50 and pharmacy (n = 14) 22,24‐26,28,29,31,41,43,44,50‐53 . A large number of studies were undertaken in the United States of America (n = 24), 22‐25,28‐33,36‐41,45,49‐52,54‐56 with a smaller number from Australia (n = 4), 34,43,57,58 Canada (n = 3) 53,59,60 and the United Kingdom (n = 2) 42,47 (see Appendix ).…”
Section: Resultsmentioning
confidence: 99%
“…To avoid the detrimental effects of collinearity on a regression mode, several methods have been suggested. Redundant collinear or duplicate explanatory variables are often removed [ 36 , 37 ]. Collinear variables can also be combined into a single index.…”
Section: Discussionmentioning
confidence: 99%